Research Progress in Oligosaccharins - Yin, Heng; Du, Yuguang (Springer New York : Imprint: Springer, 2016)
"Research Progress in Oligosaccharins" is a valuable tool for students and researchers who want to learn about this unique class of bioactive compounds. This book provides important insight into the complex roles of oligosaccharins in plant immunity, physiology, and protection. Oligosaccharins are complex carbohydrates that function in plants as molecular signals to regulate growth, development, and stress resistance. Based on the rapid development of glycobiology and molecular biology, a great deal of research work focused on oligosaccharins has been carried out in the last thirty years. As a result, several different oligosaccharins such as chitosan oligosaccharides, chitin oligosaccharides, glucan oligosaccharides, alginate oligosaccharides have been identified and their mechanisms of actions studied. Although major recent advancements have been made, there isn't an up-to-date systemic overview on the topic. Our objective is therefore to create a work that informs the reader of the nature of oligosaccharins, the different kinds of oligosaccharins, their functions and the mechanism of oligosaccharins-plants interaction.